First halogen and phosphorus-free, flame-retardant benzoxazine thermosets derived from main-chain type bishydroxydeoxybenzoin-based benzoxazine polymers. (10th October 2018) - Chen, Chien-Han; Lin, Ching-Hsuan; Hon, Jia-Min; Wang, Meng-Wei; Juang, Tzong-Yuan
Abstract: Because of wide applications in electronic industries, such as printed circuit board or encapsulation, the demand for flame retardant polymers is high. In this work, we take advantage of the flame retardant characteristic of bishydroxydeoxybenzoin (BHDB) to develop flame-retardant materials. For this purpose, three main-chain type benzoxazine polymers (MCBPs) were successfully prepared from the Mannich condensation of BHDB, paraformaldehyde, and three typical aromatic diamines: 4, 4′-diaminodiphenyl methane, 4, 4′-diaminodiphenyl ether, and 2, 2-bis[4-(4-aminophenoxy)phenyl]propane. The thermosetting films of these MCBPs show flexibility and very high modulus at high temperature (E'>8 × 10 8 Pa at 350 °C). They exhibit very high thermal stability and char yield, and belongs to UL-94 VTM-0 grade. To the best of our knowledge, they are the first benzoxazine thermosets that belong to UL-94 VTM-0 without halogen and phosphorus in the structure. Graphical abstract: Highlights: Three kinds of main-chain type bishydroxydeoxybenzoin-based benzoxazine polymers (MCBPs) were successfully prepared. The resulting thermosetting films show flexibility and high modulus at high temperature. The resulting thermosetting films exhibit high thermal stability and char yield, and belongs to UL-94 VTM-0 grade. First benzoxazine thermosets that belong to UL-94 VTM-0 without halogen and phosphorus were prepared in this work.